Computer Assisted Instruction (CAI) Drill and Practice to Improve Spatial Orientation Ability - Raksanegara, Fadel; Nurjanah, Nurjanah; Dahlan, Jarnawi Afgani (Department of Mathematics, Universitas Negeri Semarang, 2023)
This study aimed to examine the quality of improving students' spatial orientation skills through CAI (Computer Assisted Instruction) drill and practice. This study included experiments with the Non-Equivalent Control Group Design involving students at SMPN 18 Bandung selected by teacher, with 29 students in the experimental class and 26 students in the control class. The instrument used was a spatial orientation ability test instrument. The results of this study concluded that (1) the quality of improving the spatial orientation abilities of students who received CAI drill and practice was moderate, and the quality of improving spatial orientation abilities who received conventional learning was low. (2) the increase in the spatial orientation ability of students who get CAI drill and practice is higher than students who get conventional learning.